2015
DOI: 10.17474/acuofd.93758
|View full text |Cite
|
Sign up to set email alerts
|

Plumbago europaea L.’ nın Besinsel, Antioksidan ve Antimikrobiyal Aktivitesinin Belirlenmesi

Abstract: ÖzetBu çalışmada; P. europea'nın besinsel içerikleri, antioksidan ve antimikrobiyal etkileri araştırıldı. Şeker, flavonoid, vitamin ve mineral element düzeylerinin değişebildiği gözlendi. In vitro koşullarda, DPPH radikalini temizleme aktivitesinin 10 µg/µL'de %83.62, FeCl grubunun K grubuna göre yüksek ve metil esterlerinin ise korunmadığı belirlendi. P. europea'nın antimikrobiyal aktivitesinin ise; maya ve dermofit funguslardan ziyade, bakteri gruplarında daha etkili olduğu saptandı.Anahtar kelimeler: Antimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…A study conducted by Bircan and Kirbag [49] evaluated the antioxidant activity of P. europaea growing in Turkey using DPPH assay and found that it was 83.62 µg/ ml, while in the studied P. europaea growing in Palestine it was 21.38 µg/ml which exhibited an antioxidant activity four times better than that of the Turkish P. europaea [49]. In fact, the impact of the flavonoid content on antiaging and anti-lipase activities was documented.…”
Section: Discussionmentioning
confidence: 98%
“…A study conducted by Bircan and Kirbag [49] evaluated the antioxidant activity of P. europaea growing in Turkey using DPPH assay and found that it was 83.62 µg/ ml, while in the studied P. europaea growing in Palestine it was 21.38 µg/ml which exhibited an antioxidant activity four times better than that of the Turkish P. europaea [49]. In fact, the impact of the flavonoid content on antiaging and anti-lipase activities was documented.…”
Section: Discussionmentioning
confidence: 98%